STRATEGI KOMUNIKASI HARIAN UMUM OKU EKSPRES DALAM MENINGKATKAN MINAT BACA PADA MEDIA ONLINE WWW.OKES.CO.ID - Sunday One Dharma Putra; Yunizir Djakfar; Darwadi MS (Universitas Baturaja, 2020)
Public interest in reading has now been different in the modern era. The media currently contains a great deal of literature and book publishers and does not affect people's interest in reading. Before the modern era, when the facilities were still limited the people at that time had high enthusiasm and motivation to read. By reading, people can get knowledge quickly and easily because they just have to choose the book to read, open it and start reading words. This research theory is Information Seeking Theory. Where this theory explains the search, sensing and processing of information, Information Seeking Theory is a process or activity that tries to obtain information from Technology in both the Human context. The importance of strategy in increasing interest in reading to the survival of the Daily Newspaper is very fierce competition. This research is a descriptive qualitative research. The research site was conducted at the Oku Ekspres Baturaja Daily. Data collection techniques to find out the results of this study through in-depth interviews. After conducting interviews with informants it can be seen that the Oku Ekspres Daily Communication Strategy in Increasing Reading Interest in Okes.co.id Online Media requires that the Strategy used now in the Oku Ekspres Daily Daily is to utilize online media as a means of supporting success in increasing reading interest for the readers. Considering this research is related to the Communication Strategy, which this strategy was carried out to attract the attention of the readers.